2006
DOI: 10.1038/sj.ijo.0803350
|View full text |Cite|
|
Sign up to set email alerts
|

Differential association of C-reactive protein with adiposity in men and women in an Aboriginal community in northeast Arnhem Land of Australia

Abstract: Objective: To examine the relationship between C-reactive protein (CRP), adiposity and other metabolic abnormalities in an Aboriginal community in Northern Australia. Design: Cross-sectional analysis of data obtained between 2001 and 2003 from 379 Aboriginal people residing in a geographically isolated community. Results: Mean (95% CI) CRP in women and men was 4.06 cholesterol (3.53, 4.66) mg/l and 3.42 (2.94, 3.97) mg/l, respectively (P ¼ NS). The prevalence of the metabolic syndrome (US National Education pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
(37 reference statements)
8
32
1
2
Order By: Relevance
“…Waist circumference has been shown to be among the strongest correlates of CRP across a wide range of populations, consistent with the established importance of visceral adipose tissue as a source of proinflammatory cytokines (32,33). However, several studies have documented sex differences in patterns of association between CRP and waist circumference and other measures of adiposity (34)(35)(36). The Pelotas Birth Cohort Study in Brazil, for example, reported stronger associations between central obesity and CRP in young adult women than in young men (37).…”
Section: Discussionmentioning
confidence: 94%
“…Waist circumference has been shown to be among the strongest correlates of CRP across a wide range of populations, consistent with the established importance of visceral adipose tissue as a source of proinflammatory cytokines (32,33). However, several studies have documented sex differences in patterns of association between CRP and waist circumference and other measures of adiposity (34)(35)(36). The Pelotas Birth Cohort Study in Brazil, for example, reported stronger associations between central obesity and CRP in young adult women than in young men (37).…”
Section: Discussionmentioning
confidence: 94%
“…Elevated CRP has been previously reported to be strongly associated with central obesity in remote Aboriginal populations (25), which in turn may be associated with hyperfiltration and thus eGFR decline. The potential role of central obesity is supported by a recent report that percentage body fat (rather than weight) was independently associated with eGFR decline in 615 healthy Koreans (26).…”
Section: Discussionmentioning
confidence: 99%
“…The research design and methods are reported in detail elsewhere (4 ). Briefly, we screened 70 participants living in an isolated coastal Aboriginal community in the northeast of Arnhem Land in 2 risk-factor screening programs between 2001 and 2004.…”
Section: Methodsmentioning
confidence: 99%